1987
DOI: 10.1021/ma00172a029
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition of submicron gel beads

Abstract: A phase transition of spheres of ionized N-isopropylacrylamide gels with diameters ranging from 0.2 to 1 fim has been observed with photon correlation spectroscopy. The submicron gels undergo a sharp, but continuous volume phase transition in water in response to temperature change. The transition temperature depends on the degree of ionization of the gel and is approximately 34 "C for a nonionic gel and 38 "C for a gel with 4.5% ionizable groups. The volume change at transition increases with ionization of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
1
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(100 citation statements)
references
References 5 publications
(7 reference statements)
2
95
1
2
Order By: Relevance
“…A value for the nickel(II) complex (9b) could not be measured because of the fast solubilization in water. On the other hand, iron(II) (9a) and ruthenium(III) (9d) complexes were stable and the swelling degrees could be measured without the apparent disappearance of the polymer networks by immersion in water for 24 h. These values (about [15][16][17][18] were close to each other and were in good agreement with the results of the degrees of swelling of a series of the functionalized PAEis 35 (Table II).…”
Section: The Effect Of Metal Ions On the Stability Of The Gelssupporting
confidence: 84%
See 1 more Smart Citation
“…A value for the nickel(II) complex (9b) could not be measured because of the fast solubilization in water. On the other hand, iron(II) (9a) and ruthenium(III) (9d) complexes were stable and the swelling degrees could be measured without the apparent disappearance of the polymer networks by immersion in water for 24 h. These values (about [15][16][17][18] were close to each other and were in good agreement with the results of the degrees of swelling of a series of the functionalized PAEis 35 (Table II).…”
Section: The Effect Of Metal Ions On the Stability Of The Gelssupporting
confidence: 84%
“…The generality of these phenomena has been investigated extensively by Tanaka's group. 17 In aqueous salts, the swelling degrees of these ionic hydrogels are known to be diminished largely in comparison with those of non-ionic hydrogels made from poly(oxyethylene) 18 or po I y( a cry !amide). 1 9…”
Section: Cross-linkingmentioning
confidence: 99%
“…Polyelectrolyte hydrogels exhibit unique stimuli responsive physical properties, [1][2][3][4][5][6][7] and which have been widely utilized for many engineering applications including actuators, drug delivery and sensors. [8][9][10][11][12][13] Because the degree of charge dissociation in polyelectrolytes is dependent on the types of ion-pairs, the physical properties of polyelectrolyte hydrogels such as conductivity, elasticity and swelling ratio are affected by counterions as well as external stimuli.…”
Section: Doi: 101002/adma201103767mentioning
confidence: 99%
“…Indeed, the poly(N-isopropylacrylamide-co-methacrylic acid) (PNIPA-MAA) microgel particles [22] at pH 3.4 exhibited a decrease in Tc from 33.5 to 28 C with an increase in MAA content, whereas at pH 7.5, the higher MAA content resulted in the higher Tc. In weakly charged PNIPA hydrogels, addition of ionizable groups on the polymer network pronounced the volume changes when temperature crossed Tc [21,23,24]. The experimental studies [25] revealed that even distribution of ionic groups in the network affects the temperature of volume change transition.…”
Section: Effectors Of Volume Change In Hydrogelsmentioning
confidence: 99%